A Performatory Approach to Teaching, Learning and Technology - Martinez, Jaime E.; SpringerLink (Online service) (Rotterdam : SensePublishers, 2011)
Even the most cursory glance at innovation in the field of education will reveal the emerging importance that researchers place on play, performance and collaboration in the classroom. Concurrently policy makers and school districts are investing more resources in promoting the development of 21st Century skills and technology use in the classroom. A Performatory Approach to Teaching, Learning and Technology integrates technology use in teaching and learning and the use of a Vygotskian performance-based pedagogy. Through the use of ethnographic vignettes and narratives the development of the author$1 (Bs teaching practice is presented as challenges and contradictions brought about by technology use and a humanistic perspective on teaching and learning are engaged. The performatory social therapeutic framework that the author$1 (Bs teaching practice is grounded in is richly illustrated with scenes from elementary, middle school and undergraduate classrooms. The featured technologies include laptops, Internet-based applications, course management systems, discussion forums, e-mail, digital video, Wiki$1 (Bs and Blogs. Audience: Teachers, first year graduate students and researchers will be interested in this book for a practitioner$1 (Bs perspective on the integration of an innovative pedagogy and technology into teaching practices.s
Keywords: Education; Education; Learning & Instruction